Honokiol and its analogues as anticancer compounds: Current mechanistic insights and structure-activity relationship - Prasher, Parteek; Fatima, Rabab; Sharma, Mousmee; Tynybekov, Bekzat; Alshahrani, Asma M.; Atessahin, Dilek Arslan; Calina, Daniela (Elsevier Ireland Ltd, 2023)
Lignans are plant-derived polyphenolic compounds with a plethora of biological applications. Also, regarded as phytoestrogens, the lignans offer a variety of health benefits of which the anti-cancer effects are the most attractive. Honokiol is a lignan isolated from various parts of trees belonging to the genus Magnolia. The bioactivity of honokiol is attributed to its characteristic physical properties, which include small size and the presence of two phenolic groups that may interact with proteins in cell membranes via hydrophobic interactions, aromatic pi orbital co-valency, and hydrogen bonding. The hydrophobicity of honokiol enables its rapid dissolution in lipids and the crossing of physiological barriers, including the blood-brain barrier and cerebrospinal fluid. These factors contribute towards the high bioavailability of honokiol which further support its candidature in medicinal research. Therefore, the anticancer properties of honokiol are of particular interest as many of the contemporary anticancer drugs suffer from bioavailability drawbacks, which necessitates the identification and development of novel candidate molecules directed as anticancer chemotherapeutics. The antioncogenic profile of honokiol also arises from the regulation of various signalling pathways associated with oncogenesis, arresting of the cell cycle by regulation of cyclic proteins, upregulation of epithelial markers and downregulation of mesenchymal markers leading to the inhibition of epithelial-mesenchymal transition, and preventing the metastasis by restricting cell migration and invasion due to the downregulation of matrix-metalloproteinases. In this review, we discuss the anticancer properties of honokiol.
Keywords: Honokiol; Cancer; Signalling pathways; Molecular mechanisms; Structure -anticancer activity relationship; Apoptosis